Growth and Characterization of Diamonds for Use in High Pressure Sensing - Hamel, Michael Tokiyoshi (Université d'Ottawa / University of Ottawa, 2022)
Diamond possesses unique physical properties which give it great potential as a solid state framework for quantum sensors. Despite a worldwide research and development effort, the primary factors limiting its wider implementation are the technical difficulties related to high quality synthesis and device manufacture. In this work, as a first objective, laboratory diamond synthesis is explored with the aim to achieve single crystal diamond of high quality. A suite of characterization methods is implemented to evaluate and understand the physical qualities of synthesized diamond. Through a measurement process, a procedure for improving diamond growth is presented. As a secondary objective, a diamond-based defect which can be functionalized as a quantum sensor is investigated. The negatively charged silicon vacancy defect (SiV⁻) in diamond is explored for its potential use as a quantum high pressure/low temperature sensor. This SiV⁻ defect is optically accessible by photoluminescence. This optical emission arising from the SiV⁻ defect is studied under high pressures (up to 17 GPa) and low temperatures (down to 11 K). More specifically, the emission corresponding to SiV⁻ zero phonon line and local vibrational mode and their respective change as a function of pressure and temperature are recorded. This work indicates a promising potential for the SiV⁻ defect as a useful quantum sensor, especially in the context of extreme conditions research.
Keywords: Diamond; Pressure; Silicon; Vacancy; Growth; Plasma; Extreme; Temperature; Sensor; Microwave; Chemical; Vapor; Deposition; Color; Center; Synthesis; Defect; Photoluminescence